A Pliocene to recent history of the Bering Sea at Site U1340A, IODP Expedition 323. (26th December 2015) - Stroynowski, Zuzia; Ravelo, Anna Christina; Andreasen, Dyke
Abstract: Fossil diatoms are the principal component of Bering Sea sediments and reflect the paleoceanographic history of the region. Diatom accumulation rates and relative abundances at International Ocean Discovery Program (IODP) Site U1340A are presented. Overall, the total diatom productivity record from 4.9 Ma to the present day reveals a fourfold reduction at circa 4.2 Ma from 45 × 10 7 down to 11 × 10 7 valves/g (wet sediment), signifying a major shift in the upwelling and/or nutrient regime, coinciding with the end of the late Miocene‐early Pliocene bloom identified in the eastern equatorial Pacific and California margin. Further abrupt shifts in the diatom assemblage occur at (1) 2.78–2.55 Ma, (2) 2.0–1.8 Ma, and (3) 1.0–0.88 Ma. (1) At 2.78–2.55 Ma, the appearance of sea ice‐related species marks the regional cooling associated with the expansion of Northern Hemisphere ice sheets, subsequent development of stratified, nutrient‐depleted waters, and increased influence of Western Basin Water masses (most likely due to the suppressed inflow of the Alaskan Stream). (2) Rapid cooling between 2.0 and 1.8 Ma indicates increased sea ice duration and/or frequency. This, coupled with low sea level stands caused prolonged closure of the Aleutian Passes, coupled with further increased Western Basin Water inflow. (3) The shift to 100 ka glacial/interglacial cycles at the middle‐Pleistocene transition (1.0–0.88 Ma) marked an increase in upwelling‐related species, indicating enhanced surface water mixing. These records confirm that the development and changing dynamics of sea ice in the Bering Sea played a major role in sub‐Arctic Ocean circulation and is an integral component of global climate change. Key Points: Enhanced silica deposition during the Early Pliocene No evidence of sea ice prior to 2.65 Ma Shift in species assemblage at 1 Ma related to intensification of sea ice